An analysis of the effect and influence of macroeconomic factors on 10-year government bond Yields in the ASEAN-4 - Andres, Dan Joseph L. (Animo Repository, 2023)
This study analyzes the relationship of macroeconomic indicators with the yields of 10-year sovereign bonds in the ASEAN-4. The ASEAN-4 comprises Indonesia, Malaysia, the Philippines, and Thailand. The study has the objective of determining whether economic metrics are correlated with the yields of 10-year government bonds. A multiple linear regression analysis was conducted to answer the research questions and address the objectives of the study. Inflation rate proved statistically significant to bond yields in Malaysia, the Philippines, and Thailand. Oil prices are significant with the yields of Thai and Philippine bonds. Gold price is correlated to the yields of government bonds in Indonesia and Malaysia. The foreign exchange variable has a relationship with Indonesian government bond yields. The world uncertainty index has a relationship with the bond yields in the Philippines and Thailand. The economic growth variables, GDP per capita, savings, and foreign direct investment, were found to have no relationship with bond yields. However, in the regression analyses of the Philippines and Thailand, the savings variable was omitted due to the refitting of the models.